THE EFFECT OF TEACHING QUALITY AND LEARNING FACILITIES ON THE SATISFACTION OF POSTGRADUATE STUDENTS SEMESTER 2 OF UNIVERSITY X - Andriani Sariwardani; Siti Arofa; Mutoharoh; Umalihayati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This research is motivated by the increasing competition of universities in Indonesia, so that the quality of teachers and learning facilities become important factors in determining student satisfaction. The purpose of this study is to analyze the effect of the quality of teachers and learning facilities on the satisfaction of 2nd semester students at University X. The method used is quantitative with a survey technique using a questionnaire to 80 respondents, who were selected through the Slovin formula from a population of 100 students. Data analysis was carried out by testing validity, reliability, coefficient of determination, and t and F tests. The results of the study showed that the quality of teachers and learning facilities had a significant effect on student satisfaction, with a partial contribution of 75.3%. In conclusion, improving the quality of teachers and learning facilities is very important to increase student satisfaction in higher education.